Peran Gender Dan Interval Puasa Pada Profil Lipid Tikus Wistar Dengan Diet Atherogenik - Rahma triliana; Hardadi Airlangga (Jurnal Kesehatan Islam : Islamic Health Journal, 2018)
Introduction: Atherogenic diet can induced.hyperlipidemia leading to abnormal lipid profile. Time restricted feeding is proposed as treatment for hyperlipidemia. However, the effect of gender and which type of time-restricted feeding is the best to alter lipid profile is unknown.Method: The study was conducted in female and male wistar rats which was devided into 5 groups, Negative Control (KN, n=8), Positive Control (KP, n=8), Daily restricted group (KRam, n=8), alternate restricted group (KDaud, n=8) and Monday-Thursday restricted group (KSeKa, n=8) respectively. Atherogenic diet were administrated for six weeks followed by 4 weeks of time-restricted feeding. At 15 weeks of age, all rats were humanely culled and serum samples were collected for analyses. Lipid profile were assesed using spectrophotometry and analysed using two way Anova followed by post hoc LSD and p < 0.05 is considered as statiscally significant.Results: Gender and time restricted feeding affects serum total cholesterol and non-HDL cholesterol levels while gender influenced HDL and time restricted feeding influenced LDL levels. Both gender and time restricted feeding did not altered trigliseride level. Interestingly, no significant differences were found in lipid profile of KN vs KP in male or female group. Time restricted feeding had no significant effect in male but significant effect on female with higher, undesireable lipid profile.Conclusion: Atherogenic diets did not lipid profile in male or female rats, but higher lipid profile were observed in female with atherogenic diet. Time restricted feeding has gender related effect cholesterol and non-HDL cholesterol level, but no gender effect on LDL. HDL is solely dependent on gender and not affected by atherogenic diet or time restricted feeding.